Democracy in Retreat: The New Media and Human Rights Dimension to Covid-19 Pandemic in Nigeria (Journal of Advanced Research in Social Sciences, 2023)
The role of the new media in analyzing and monitoring the global pandemic of Covid-19, which reveals at the same time reveals inadequacies of ensuring human rights in Nigeria cannot be over-emphasized. As an outlet for information gathering and dissemination, the media provided citizens with developments surrounding the Covid-19 pandemic. While identifying the power of media during the pandemic, this paper seeks to examine the human rights perspective of the Nigerian government. It argues that rather than the Nigerian Federal Government promoting the human security associated with the practice of democracy; freedom and liberty, transparency and legitimacy of governance; rule of law, and equity for citizens; settles for authoritarian governance that violates the democratic principles and human rights tenets. Primary data is sourced from social media platforms of television and radio stations; and social media influencers from entertainment and politics. Secondary data is gathered from consultations with journal articles, books, and newspapers. Findings are analyzed using content analysis; needed to blend the objectives of the paper.